Analisis Kritis terhadap Implementasi Undang-Undang ITE di Indonesia: Menimbang Kembali Kepastian Hukum dan Perlindungan Kebebasan Sipil di Era Digital - Gilang Rizki Aji Putra (BULETIN ADALAH, 2021)
The Electronic Information and Transactions Law was enacted to ensure legal certainty in digital activities. However, its implementation has generated controversy due to vague provisions and repressive enforcement. This article critically examines its application in Indonesia, focusing on controversial articles, impacts on freedom of expression, and the effectiveness of revisions. Using normative legal research with statutory, conceptual, and case approaches, the study finds persistent weaknesses, including unclear norms (lex certa) and risks of criminalization. Despite adopting ultimum remedium, enforcement practices remain problematic. Strengthening legal guidelines and judicial oversight is essential. Keywords: Electronic Transactions Law, Legal Certainty, Criminalization, Lex Certa, Freedom of Expression